Math, asked by mallikaborah77, 10 months ago

solve the equation 3-5x+2x=-2-2(1-x)​

Answers

Answered by rashmitrial95
1

Answer:

SOLUTION: How to solve this equation 3-5x+2x=-2-2(1-x) The first thing we need to do is distribute the -2(1-x) we do this by multiplying the -2 by both 1 and -x. We are going to put our x's on the left side now: 3-5x+2x-2x Remember, when the x's or numbers cross the equals sign, change the sign!

Answered by shinegoyal
0

Answer:

3-5x+2x=-2-2(1-x) \:  \\ 3 \:  + \:  2\:  +  \: 2 \: \:  -  \: 1 \:  =  \: 5x \:  - 2x \:  -  \: x \\  6 \:  =  \: 8x \\  \frac{6}{8}  \:  =  \: x \\   \frac{3}{4} \:  = x \\ x \:  =  \frac{3}{4} ans

Similar questions